CA27.29 as a tumour marker for risk evaluation and therapy monitoring in primary breast cancer patients - Rack, Brigitte K.; Schneeweiss, Andreas; Beckmann, Matthias Wilhelm (Tumor biology, 2016)
Several trials showed that tumour markers are associated with an impaired prognosis for breast cancer. Whether earlier treatment can improve the course of the disease remains controversial. The SUCCESS Trial compares FEC (500/100/500)-docetaxel (100) vs. FEC (500/100/500)-docetaxel/gemcitabine (75/2000) as well as 2 vs. 5 years of zoledronate in high-risk primary breast cancer patients. In 2669 patients, CA27.29 was measured before and after chemotherapy with the ST AIA-PACK CA27.29 reagent for the AIA-600II automated enzyme immunoassay (Tosoh Bioscience, Belgium). Values above 31 U/ml were considered positive. Of the patients, 7.6 % (n = 202, mean 19, range 3-410) and 19.1 % (n = 511, mean 21, range 3-331) had elevated marker levels before and after chemotherapy, respectively. Of the patients, 4.9 and 78 % showed elevated and low CA27.29, respectively, at both time points. After treatment, 35 % of the pre-therapy positive patients were negative, and 15 % of the initially negative patients became positive. The correlation between both time points was significant (p < 0.0001). No correlations among nodal status, grading, hormonal status, HER2 status and CA27.29 levels were found. However, tumour size (p = 0.02), older age (p < 0.001) and post-menopausal status (p = 0.006) were significantly associated with higher CA27.29 levels. Before treatment, the prevalence of elevated CA27.29 was equally distributed between both treatment arms, whereas after chemotherapy, 13.7 % of the patients in the FEC-doc arm showed an increased level vs. 25.4 % of the patients in the FEC-doc/gemcitabine arm (p < 0.0001). However, we could not show a significant association between the G-CSF application (yes vs. no) and CA27.29 status before/after chemotherapy (p = 0.75). These results indicate a close relationship between CA27.29 levels and tumour mass. Increased values after the completion of chemotherapy might be attributed to treatment effects and should be considered with caution.
Gesehen am 22.11.2017